Reliability Estimation based on Step-Stress Accelerated Degradation Testing by Unequal Interval Time Series Analysis - Li Wang; Zaiwen Liu; Chongchong Yu (Institute of Advanced Engineering and Science, 2013)
This paper proposes a reliability estimation method based on Step-Stress Accelerated Degradation Testing (SSADT) data analysis using unequal interval time series analysis. A Multi-Regression Time Varying Auto-Regressive (MRTVAR) degradation time series model is proposed. Product SSADT data are treated as unequal interval composite time series and described using MRTVAR time series model and utilized to predict long-term trend of degradation. By using the suggested method, product reliability is obtained. An example is presented as a verification of the modeling technique and estimation method. A reasonable estimation of lifetime and reliability of the product is obtained by employing the present method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3402